2015
DOI: 10.1007/s00167-015-3569-9
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic single-bundle anterior cruciate ligament reconstruction with six-strand hamstring tendon allograft versus bone-patellar tendon-bone allograft

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 49 publications
1
42
0
1
Order By: Relevance
“…Recent studies showed that the thicker graft has a lower failure rate for ACL reconstruction [ 20 22 ]. However, the width of the grafts should be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the thicker graft has a lower failure rate for ACL reconstruction [ 20 22 ]. However, the width of the grafts should be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous different hamstring preparation techniques have been described in the literature. 9 , 23 There is, however, a scarcity of studies looking at superiority within hamstring graft types. Conte et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthering the argument that larger graft size leads to improved outcomes, the study by Dai et al. 9 showed that a 6-strand hamstring tendon autograft had decreased pivot shift, less graft failure rate, and improved KT-1000 outcomes when compared with a patellar tendon autograft. Although studies like these help to make the argument that larger graft size with more strands may lead to increased anteroposterior stability, they do not say anything regarding long-term outcomes, and rates of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several options as to reconciling this situation intraoperatively, including (1) abandoning the diminutive graft and using an all allograft concept, (2) using the autograft available and augmenting this with an allograft, or (3) using a 5-or 6strand construct if the semitendinosus is of appropriate size. 8,9 Leo et al reported on their use of a nonirradiated soft tissue allograft (tibialis anterior or tibialis posterior) to supplement the autograft harvested and achieve a minimum graft size. International Knee Documentation Committee and UCLA ACL quality of life scores demonstrated no statistical difference between the groups at a minimum of 2 years of follow-up.…”
Section: See Related Article On Page 2357mentioning
confidence: 99%